2007
DOI: 10.1104/pp.106.094995
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioinformatics Approach Identifies Candidate Genes for the Synthesis and Feruloylation of Arabinoxylan

Abstract: Arabinoxylans (AXs) are major components of graminaceous plant cell walls, including those in the grain and straw of economically important cereals. Despite some recent advances in identifying the genes encoding biosynthetic enzymes for a number of other plant cell wall polysaccharides, the genes encoding enzymes of the final stages of AX synthesis have not been identified. We have therefore adopted a novel bioinformatics approach based on estimation of differential expression of orthologous genes between taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(239 citation statements)
references
References 38 publications
5
234
0
Order By: Relevance
“…This result suggests arabino-(1→4)-b-D-xylan in this region is in a highly substituted form that the LM11 antibody does not recognize. Consistent with this, members of the GT43 and GT47 gene families, which have been implicated in arabino-(1→4)-b-D-xylan synthesis in other plant systems (Mitchell et al, 2007;York and O'Neill, 2008;Zeng et al, 2008) were transcribed throughout the developmental window used in this study (Fig. 11E).…”
Section: Arabino-(1→4)-b-d-xylansupporting
confidence: 60%
See 3 more Smart Citations
“…This result suggests arabino-(1→4)-b-D-xylan in this region is in a highly substituted form that the LM11 antibody does not recognize. Consistent with this, members of the GT43 and GT47 gene families, which have been implicated in arabino-(1→4)-b-D-xylan synthesis in other plant systems (Mitchell et al, 2007;York and O'Neill, 2008;Zeng et al, 2008) were transcribed throughout the developmental window used in this study (Fig. 11E).…”
Section: Arabino-(1→4)-b-d-xylansupporting
confidence: 60%
“…We have examined the monosaccharide composition of the endosperm over the course of development, applied the recently generated xyloglucan antibody to early endosperm development, and modified our approach to studying arabino-(1→4)-b-D-xylan using the LM11 antibody. Previous studies identifying genes involved in the synthesis of cell wall polysaccharides have shown that transcript accumulation correlates with the time of polysaccharide synthesis and deposition (Pear et al, 1996;Doblin et al, 2001;Dhugga et al, 2004;Brown et al, 2005;Persson et al, 2005;Cocuron et al, 2007;Mitchell et al, 2007). By coupling our immuno-EM observations with transcript profiles of candidate cell wall synthesis genes, we can now infer which subfamily members of these gene families is functional during key stages of endosperm development.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, it has been shown recently that GAUT1, a type II galacturonyltransferase of the GT8 family, is capable of mediating the synthesis of the homogalacturonan backbone of pectic polysaccharides (Sterling et al, 2006). Similarly, type II GTs have been implicated in the synthesis of the (1,4)-b-D-xylan backbone of heteroxylans of the wall (Lee et al, 2007;Mitchell et al, 2007;Pena et al, 2007).…”
mentioning
confidence: 99%